Complications of Biliary Atresia in a 27-Year-Old Male Patient - Nata Pratama Hardjo Lugito; I Gede Resmino Tyasto; Purwita Wijaya Laksmi (The Indonesian Society for Digestive Endoscopy, 2013)
Biliary atresia (BA) is a disease of the extrahepatic biliary tree that presents with biliary obstruction in the neonatal period, which is caused by fibro-obliterative process. Kasai procedure, a hepatoportoenterostomy(HPE) as an attempt to restore bile flow from the liver to the proximal small bowel, has been shown to improve survival in BA patients. Many BA survivals who had undergone Kasai HPE will have slowly progressive liverdisease and the majority of patients will ultimately require liver transplantation. In spite of many experimental treatments, cirrhosis still occurs in BA patients survival.This case report presents a male patient with biliary atresia that has survived for 27 years after Kasai procedure. He had been repeatedly admitted to hospital with complications caused by cirrhosis, such as repeated variceal and hemorrhoid bleeding and also refractory ascites. These complications are indications for liver transplantation. Although Kasai HPE procedure improves survival in BA patients in Indonesia, long-termcomplications of cirrhosis makes the patient awaits for liver transplantation. Keywords: biliary atresia, Kasai procedure, hepatoportoenterostomy, cirrhosis, liver transplantation